All fibre Q-switched Thulium-doped fibre laser incorporating Thulium–Holmium co-doped fibre as a saturable absorber - Wang, Pengfei; Li, Shi; Yin, Yu; Lewis, Elfed; Garrell, Gerald; Rosol, Ahmad Haziq Aiman; Abdul Latiff, Anas; Harun, Sulaiman Wadi; Guo, Bingang (Elsevier, 2019)
A novel all fibre Q-switched Thulium-doped fibre laser (TDFL) is reported which includes a short length of a Thulium–Holmium co-doped fibre (THDF) as a saturable absorber. A high repetition rate (27.26 kHz) coupled with a low pulse width (19.06 μs) is obtained for single wavelength Q-switched pulse operation at an output wavelength of 1911.5 nm using a pump power of 200 mW. Increasing the pump power from 200 mW to 700 mW results in the repetition rate increasing from 27.26 kHz to 99.67 kHz and the pulse width decreasing from 19.06 μs to 920 ns. The centre wavelength of the single Q-switched pulse was also red shifted from 1911.5 nm to 1932.5 nm with increasing the pump power. A 45 m length single-mode fibre (SMF-28) provided dispersion compensation, and effectively an SMF-THDF-SMF structure is inserted in the cavity which operates in a similar manner to an SMF-MMF-SMF structure, providing a strong multimode interference effect which supports dualwavelength operation. A stable dual-wavelength Q-switched pulse was achieved at a threshold pump power of 213 mW. The dual-wavelength Q-switched pulse operation was generated at 1911.5 nm and 1914.5 nm with a repetition rate of 8.45 kHz and pulse width of 20.02 μs. The dual-wavelength spacing of this pulse operation was 3 nm, which was in good agreement with calculations based on the multimode interference effect induced by the THDF. The repetition rate increased from 8.45 kHz to 70.65 kHz and the pulse width decreased from 20.02 μs to 870 ns with increasing pump power. At the maximum pump power of 700 mW, the maximum output power was measured as 27.4 mW. The experimental results confirm that the THDF can be utilized as a SA to generate a stable and tunable single-wavelength Q-switched pulse output as well as dual-wavelength Q-switched pulse in the 2.0 μm wavelength region.